The Cardiac Output Monitoring EvaluaTion –UK (COMET-UK) study. (January 2014) - Ridley, Saxon; Harrison, David A; Walmsley, Emma; Harvey, Sheila; Rowan, Kathy M
The aim of the Cardiac Output Monitoring EvaluaTion-UK (COMET-UK) study was to update reports of cardiac output (CO) monitoring use and to examine whether there is any association between the frequency of CO monitoring use in adult, general intensive care units and patient outcomes. Questionnaires were sent to all intensive care units in England, Wales and Northern Ireland (n=221) asking whether the unit had used CO monitoring in the last two years and, if so, to give details of average frequency of use and which CO monitors were available. The majority of units (n=100, 45.2%) used CO monitoring most days or a few times a week and 33 (14.9%) monitored CO every day (response rate 100%). The most commonly available methods were oesophageal Doppler (n=127, 57.5%), LiDCO (n=96, 43.4%) and PiCCO (n=92, 41.6%). There was no significant difference in risk-adjusted acute hospital mortality (p=0.25) or length of stay (p=0.48) across categories of frequency of use. However for ventilated vs non-ventilated patients and different quartiles of illness severity, there was an association between higher frequency of use and worse outcome among non-ventilated and lowest risk admissions quartiles. The COMET-UK study found that CO monitoring is in common use; however, there was no evidence that more frequent use of CO monitoring was associated with improved outcomes.